Identificación de compuestos fenólicos en albahaca (Ocimum basilicum L.) para elaboración de repelente para Aedes aegypti. - Vázquez-García , A.; Romo-Aguirre, A. S.; Castro- Hernández, S.I.; Alba-Romero , J.J.; Martínez-Romero, A.; Niño-Castañeda , M. S.; Moran-Martínez , J.; Hernández-González , S. I (Revista de Ciencias Médicas Torreón, 2026)
This study aimed to identify phenolic compounds in Ocimum basilicum L. (basil) leaves to develop a natural repellent against Aedes aegypti, the vector of dengue, zika, and chikungunya. Essential oil was extracted through hydrodistillation using a Clevenger apparatus and compared with commercial oils. A liquid repellent was then formulated from the extracted oil, and the active compounds were identified using thin-layer chromatography (TLC), confirming eugenol as the main phenolic component. The experimental design included stability analyses at 0, 3, and 6 months, with the retention factor (Rf) used as the reference parameter. Results revealed a gradual decrease in Rf over time, indicating eugenol degradation and reduced product stability. It was concluded that basil essential oil possesses repellent potential; however, formulation adjustments in pH and storage conditions are necessary to maintain its effectiveness. This research provides experimental evidence supporting the development of sustainable, plant-based repellents as natural alternatives to synthetic products.